Pengaruh Struktur Geologi Terhadap Potensi Geodiversitas Di Daerah Sungai Klawing, Kabupaten Purbalingga-Jawa Tengah - Widagdo, Asmoro; Brahmantyo, Budi (Dinamika Rekayasa, 2014)
The Klawing River is located in Purbalingga Regency, in the central part of Central Java. The headwater of the river is in northern area of Bobotsari and flows to Serayu River as the main river. The Klawing and its tributaries cut Tertiary rocks in the mountains of North Serayu, which includes Kumbang and Tapak Formation, and Quaternary volcanic rocks of Slamet volcano. Morphology around the river is formed of volcanic mountains in the west, the steep hills sloping folds in the north and undulating plains at the east and south. Alluvial plain is produced around the Klawing river. This sediment is form terraces morphology around the main river. The main geological structures that develop in the research area is a bedding plane or the slope of the rock layers. This structure produces a typical potential distribution pattern of primary jasper at the igneous lava as well as the andesite rock mine potential. Homocline hills ranks as an object of geology is also controlled by geological structure. Geological structure of the young rocks in the study area is a horizontal bedding plane. This structure controls the distribution of sediment deposition in the secondary jasper at the terrace steps around the river.